2018
DOI: 10.1007/s13197-018-3507-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing fat by betaglucans from Ganoderma lucidum on batter and cake properties

Abstract: The aim of this study was to investigate the effects of replacing vegetable fat at different concentrations (20, 30, 40 and 50%) by betaglucans from Ganoderma lucidum (bGGL), on the physical properties of cake batters, and on the quality of the resultant cakes. The addition of bGGL significantly affected the specific gravity, the flow properties and the color of the batter formulations. The fatreplacing led to a slight reduction in the volume of cakes, because fewer air bubbles were incorporated into the batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Numerous studies in the literature suggest that as cake fat levels decrease, so does their volume. According to Lindarte Artunduaga and Gutiérrez (2019) the volume of the cake decreases when the amount of fat in the cake samples was reduced. Inulin and carrot fiber was employed by Psimouli and Oreopoulou (2017) as fat substitute.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies in the literature suggest that as cake fat levels decrease, so does their volume. According to Lindarte Artunduaga and Gutiérrez (2019) the volume of the cake decreases when the amount of fat in the cake samples was reduced. Inulin and carrot fiber was employed by Psimouli and Oreopoulou (2017) as fat substitute.…”
Section: Resultsmentioning
confidence: 99%
“…Inulin (e.g., Agave angustifolia fructans) replacement (20%) led to similar sensory properties and enhanced prebiotic activity [121]. Light microscopy images showed that, with the replacement of shortening fats with β-glucans from an edible mushroom in the batter recipe, the population of gas bubbles became decreased, with broader size distribution, which indicated the loss of stabilization by forming an interfacial lipid film along bubbles during batter forming [122].…”
Section: Milk Fats Replacementmentioning
confidence: 99%
“…It is a natural dietary fiber extracted from different plants mainly chicory roots (Shoaib et al, 2016). It is also a prebiotic and exhibits a number of health benefits in the body including decreasing the risk of many diseases of the intestinal tract, particularly irritable bowel diseases, colon cancer, and inflammatory bowel diseases (Artunduaga & Gutiérrez, 2019;Shoaib et al, 2016).…”
mentioning
confidence: 99%
“…Nonetheless, fat and sucrose replacers cannot mimic all the of techno-functional properties of sucrose and fat and hence they have some undesirable effects on the quality of the final products. For instance, fat replacement from 35% to 100% can reduce the batter viscosity and consistency and increase the batter density leading to a dense and compact cake texture with poor mouthfeel (Artunduaga & Gutiérrez, 2019;Khouryieh, Aramouni, & Herald, 2005;Lee, Kim, & Inglett, 2005;Psimouli & Oreopoulou, 2013;Rashid, Rakha, Butt, & Asgher, 2018). Inclusion of sucrose replacers such as polyols and steviol glycosides can cause a reduction in batter consistency and cake quality in terms of volume, appearance, color, and sensory properties (Gao et al, 2016;Majzoobi, Mohammadi, Mesbahi, & Farahnaky, 2018;Psimouli & Orepoulou, 2012).…”
mentioning
confidence: 99%